Eksplorasi Literasi Tumbuhan pada Siswa Sekolah Menengah Atas di Mentawai: Pendekatan Kuantitatif melalui Inventarisasi, Pengolahan, dan Pelaporan Data - aflahul, ridwan Tanjung; Sanjaya, Yayan; Solihat, Rini; Virijai, Febrian; Jasid, Adhara; Azizah, Cici Nur (JURNAL EKSAKTA PENDIDIKAN (JEP), 2025)
This study explores the plant literacy of high school students in the Mentawai Islands using a quantitative approach that integrates data inventory, processing, and reporting. A survey method was utilized, involving 302 students from three schools, to evaluate their understanding of plants across nominal, functional, structural, and multidimensional levels. Research instruments were validated for reliability with a Cronbach's Alpha of 0.973, ensuring robust data collection. Findings reveal low plant literacy levels across all dimensions, with significant challenges in identifying plants and contextualizing biodiversity concepts. The study underscores the necessity of innovative, contextual learning methods, including practical and exploratory approaches to improve plant literacy. Recommendations include integrating local biodiversity into educational curricula and promoting nature-based activities to enhance students' ecological awareness and comprehension.